2016
DOI: 10.1186/s41155-016-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome and abdominal adiposity among Primary Health Care nursing professionals

Abstract: Background: Accumulation of abdominal adiposity (AA) constitutes a risk factor for heart and coronary diseases and for metabolic complications. Research suggests that stress is related to adipogenesis. The burnout syndrome (BS) is linked to stress due to the chronicity of work stress. The objective of this study is to estimate the association between BS and AA in Primary Health Care (PHC) nursing practitioners. Methods: This is confirmatory cross-sectional study with 189 workers from nine municipalities in Bah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
11
0
7
Order By: Relevance
“…The reality is based on actions focused on the disease, fragmented work, high demand from patients/family/community, often conflicting interpersonal relationships, low wages, situations of intense suffering, and emphasis on situations of violence that are common in Brazil. These demeaning conditions predict occupational stress and BS among nursing professionals [9,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reality is based on actions focused on the disease, fragmented work, high demand from patients/family/community, often conflicting interpersonal relationships, low wages, situations of intense suffering, and emphasis on situations of violence that are common in Brazil. These demeaning conditions predict occupational stress and BS among nursing professionals [9,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The data collection instrument was the Maslach Burnout Inventory-Human Services Survey (MBI) [19], adapted and validated to Brazilian Portuguese by Tamayo [20]. It consists of 22 questions to explore the three dimensions as follows: EE (1,2,3,6,8,13,14,16,20), DP (5,10,11,15,22) and RPR (4,7,9,12,17,18,19,21). The results are scored with a five-point likert scale: "1", never; "2", rarely; "3", sometimes; "4", often; and "5", always.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, Aiken et al [25], on a sample of 10,000 nurses at hospitals in Pennsylvania concluded that 43% were emotionally exhausted. In Brazil, das Merces et al [26], on a sample of 189 Primary Health Care nursing practitioners, found that the prevalence of burnout syndrome was 10.6%. However, these results should be viewed with caution [27].…”
Section: Introductionmentioning
confidence: 99%
“…Neste contexto, verifica-se que 29,5% encontravam-se com excesso de peso, tendo seu IMC maior que 25 kg/m 2 . Apesar da pequena prevalência de adiposidade abdominal encontrada no estudo (5,3%), há na literatura estudos que apontam a plausibilidade biológica e uma associação entre o estresse e consequentemente o burnout com o aumento da adiposidade abdominal e ganho de peso 33 . Possivelmente existe uma relação entre o estresse e consequentemente a SB com o aumento de peso e adiposidade abdominal, levando a ingesta de alimentos calóricos e a estimulação do eixo Hipotálamo-Hipófise-Adrenal (HHA) e como consequência a produção de cortisol que se relaciona à obesidade visceral visando aumentar a quantidade de energia disponível para as situações de enfrentamento ao estresse [33][34][35] .…”
Section: Discussionunclassified